2011
DOI: 10.1007/s00701-010-0936-7
|View full text |Cite
|
Sign up to set email alerts
|

Are stereotactic sample biopsies still of value in the modern management of pineal region tumours? Lessons from a single-department, retrospective series

Abstract: To guide subsequent treatment, we believe that histological diagnosis is paramount. Stereotactic biopsies are currently the safest and the most efficient way of obtaining this essential information. Recent improvements in stereotactic technology (particularly robotic techniques) appear to be very valuable, with almost no permanent morbidity or mortality risk and no decrease in the accuracy rate. In our opinion, other available neurosurgical techniques (such as endoscopic neurosurgery, stereotactic neurosurgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 64 publications
2
20
0
Order By: Relevance
“…There were no deaths, infections, or permanent postsurgical sequelae. These results are in line with those of Lefranc et al 38,39 and other groups that have reported a complication rate ranging between 0% and 9.3%. 9,28,36,57 In summary, our results confirm that stereotactic biopsy under ROSA guidance combines the advantages of both frameless and frame-based methods, in terms of technical aspects, timing, and diagnostic accuracy.…”
Section: 39supporting
confidence: 93%
See 3 more Smart Citations
“…There were no deaths, infections, or permanent postsurgical sequelae. These results are in line with those of Lefranc et al 38,39 and other groups that have reported a complication rate ranging between 0% and 9.3%. 9,28,36,57 In summary, our results confirm that stereotactic biopsy under ROSA guidance combines the advantages of both frameless and frame-based methods, in terms of technical aspects, timing, and diagnostic accuracy.…”
Section: 39supporting
confidence: 93%
“…38,39 We have mainly used frameless surface registration, and bone fiducial registration only for DBS procedures, as indicated by the manufacturer. Moreover, as suggested in the literature, 5 we did not observe any influence of other factors (such as the visual system, the height of the camera from the surface, and illumination) on the robot's accuracy.…”
Section: General Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lessons from a single-department, retrospective series" by Lefranc et al [2]. The authors retrospectively analyzed a series of 88 consecutive patients who underwent stereotactic biopsies for pineal region tumors.…”
mentioning
confidence: 99%